Characterization of Streptococcus sanguis molecular receptors for Streptococcus mutans binding molecules - Deby Kania Tri Putri; Indah Listiana Kriswandini; Muhammad Luthfi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Dental caries is a major problem in oral cavity. If dental caries causes cavity, the structure of dental hard tissue will not be reversible because of damage in the structure of the hard tissue. The early pathogenesis mechanism of dental caries is an adhesion interaction between cariogenic Streptococcus mutans microorganisms and tooth surface pellicles. The attachment involves a specific molecular component interaction between the bacterial complement molecules and the surface of the host. Streptococcus sanguis as a dominant ecology at the beginning of bacterial plaque aggregation will colonize the tooth surface earlier than S. mutans. The surface of bacterial cells can express some adesin. The bacteria also can express receptors for adhesins of other bacteria. Specific receptors for adhesions of S. Mutans bacteria are not only found in the pellicles, but also present in pioneer bacteria, such as S. sanguis. Adhesion between those bacteria is called as coagregation. Purpose: This study aimed to analyze the characterization of Streptococcus sanguis molecular receptors for Streptococcus mutans binding molecules. Method: This study used a sonication method for protein isolation of S. mutans and S. sanguis bacterial biofilms, as well as electrophoresis method using 12 % SDS-PAGE gel and Western Blot analysis. Result: Results of the protein profile analysis of S. mutans biofilms using 12% SDS-PAGE showed that there were 17 bands, each of which molecular weights was 212, 140, 81, 65, 61, 48, 45, 44, 40, 39, 33 , 25, 23, 19, 17, 12, and 11 kDa. On the other hand, results of the protein profile analysis of S. sanguis biofilms using 12% SDS-PAGE showed that there were 15 bands, each of which molecular weight was 130, 85, 65, 61, 48, 46, 40, 37, 29, 25, 23, 21, 17, 15, and 12 kDa. And, results of the analysis of S. sanguis receptor molecules using Western blot showed that there were three bands, each of which molecular weight was 130, 85, and 40 kDa. Conclusion: S. sanguis bacteria have specific receptor molecules for S. mutans bacteria with the molecular weight of 130, 85, and 40 kDa.